Decision Support Tool for energy-efficient, sustainable and integrated urban stormwater management. (October 2016) - Morales-Torres, Adrián; Escuder-Bueno, Ignacio; Andrés-Doménech, Ignacio; Perales-Momparler, Sara
Abstract: The use of Sustainable Drainage Systems (SuDS) to manage urban runoff and contribute to environmental and landscape improvement is now widely known, but its application is still limited in many regions, like in Mediterranean countries. In addition, there is a lack of Decision Support Tools that consider all their benefits in the decision making process in a clear and integrated holistic way. In this paper, the E 2 STORMED Decision Support Tool is presented. This tool analyses the impact of stormwater management in the urban environment and introduces energetic and environmental criteria in the decision making process. Therefore, it aims to fill in the existing "gap" between SuDS manuals and guidelines and regional and local decision makers, since it quantifies SuDS benefits and includes them in the comparison of different stormwater scenarios. Finally, the results of applying this tool to compare drainage infrastructures in a real urban development are described. Highlights: The E 2 STORMED Decision Support Tool for stormwater management is presented. It complements financial analyses with energy and environmental criteria. It provides robust decision criteria for informed stormwater management. This tool encourages a more sustainable urban water management. The tool is very useful to promote SuDS between local and regional decision makers.